Cultural Adaptation and Support Resources among Filipino Migrant Nurses in a UK Hospital: A Descriptive Cross-Sectional Study - Jezalyn O. Vargas; Cyril B. Romero; Jane M. Tagum-Briones (The Indonesian Institute of Science and Technology Research, 2026)
Internationally recruited nurses must adapt not only to new healthcare systems but also to unfamiliar cultural and social environments. This study examined cultural adaptation and support resources among Filipino migrant nurses employed at Darlington Memorial Hospital in the United Kingdom and explored associations with selected demographic and employment characteristics. A descriptive cross-sectional survey was conducted among 26 Filipino nurses recruited through purposive sampling. Participants completed a self-developed, expert-validated questionnaire using a four-point Likert-type scale. The analysis focused on cultural adaptation and support system domains. Descriptive statistics and exploratory Pearson correlation analyses were performed. Participants reported generally favorable cultural adaptation (mean = 3.08). Managing cultural differences in the workplace received the highest rating (mean = 3.35), whereas participation in local community events was lowest (mean = 2.42). Perceived support resources were also favorable overall (mean = 3.11). Maintaining contact with family and friends in the Philippines received the highest rating (mean = 3.85), while access to housing assistance was lowest (mean = 2.46). Cultural adaptation was significantly associated with age (r = .55, p = .003), civil status (r = .64, p < .001), and length of service (r = .44, p = .026). Support resources were associated with age (r = .40, p = .041) and civil status (r = .58, p = .002). Findings suggest that workplace cultural adjustment may coexist with limited community integration and continued reliance on transnational family support. Targeted organizational support may facilitate broader adjustment.